2006
DOI: 10.1016/s0022-5347(05)00340-x
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Extraperitoneal Radical Prostatectomy: An Alternative Approach

Abstract: The extraperitoneal approach offers the advantages of improved dexterity and visualization of the robot, while avoiding the abdominal cavity and potential associated morbidity. As surgeons gain more experience with this new technology, the extraperitoneal approach simulating the standard open retropubic technique is likely to gain popularity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
75
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(84 citation statements)
references
References 17 publications
7
75
0
2
Order By: Relevance
“…The mean length of hospital stay was 4 days and comparable with other European series [18,23]. North-American series reported a shorter duration of hospitalization, essentially explained by varying international hospital practice [10,19,22,24].…”
Section: Discussionsupporting
confidence: 78%
“…The mean length of hospital stay was 4 days and comparable with other European series [18,23]. North-American series reported a shorter duration of hospitalization, essentially explained by varying international hospital practice [10,19,22,24].…”
Section: Discussionsupporting
confidence: 78%
“…The pathologic stage and PSM rates for open, RLP, and RARP series are summarized on Table 4, 16-22,24-28,30,31,33,55-57 Table 5, 33,37,38,[40][41][42][44][45][46][47] and Table 6, 30,31,35,[48][49][50][51][52][53][54]58 respectively. The pathologic stage in the RARP series was of 78.2% pT 2 tumors and 20.5% pT 3 tumors.…”
Section: Oncologic Outcomesmentioning
confidence: 99%
“…Early studies reported PSMs of 13%-35% [13,21], and contemporary studies also show relatively high PSMs in the early experience of some centres [22]. As the more experienced centres have accumulated large numbers of cases, the reported margin rates for RALRP have been reduced to overall PSM rates of < 15% and pT2 PSM rates of < 10%, which seem to be the minimum standard to which centres should aspire [10,11,23,25].…”
Section: Oncological Datamentioning
confidence: 99%